Pendampingan Digital Marketing pada Taman Rekreasi Sengkaling Malang - Praharjo, Ardik; Achmad, Mohyi; Achmad Roberth Fathoni, Rinaldy (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2022)
The potential to use information technology that is increasingly effective and efficient is one of the opportunities to be able to compete. Digital Marketing is an important part of business development. The benefits of using digital marketing are as a way to introduce and increase business productivity. Sengkaling Recreation Park also collaborates with Small and Medium Enterprises that need assistance in the use of Digital Marketing technology. The result of this assistance is to increase business potential and become a characteristic with other businesses. Based on this service, the team concluded that the use of digital marketing needs to be done intensively because of the rapid development of information technology and has an impact on Sengkaling Recreation Park